An assessment of the brassiere needs of selected plus-size women - Almazan, Michelle Roldan (College of Home Economics, University of the Philippines, 2009)
This study assessed the brassiere needs of selected plus-size women. The main objective of the study was to determine the brassiere needs of plus-size women. Specifically, the study aimed to meet the following objectives: (a) determine the common problems encountered by selected plus-size women with regards to their brassieres and (b) to identify the factors related to their purchase of brassieres. The study was conducted to determine the brassiere needs of plus-size women as well as the factors related to their purchase. Data gathering was done by conducting survey among selected plus-size women of ages 17-31 years old. Questionnaires developed by the researcher were given out to selected plus-size women. Purposive sampling was done and a total of 18 women were surveyed for the study. The results of the survey were encoded and tabulated using the frequency distribution and percentage. Linkages and trends were identified to generate a concise list of brassiere needs of plus-size women. These linkages and trends included which part of the brassiere affects the respondents the most and the factors affecting their brassiere purchase. These were then presented using a graph to serve as guide for the analysis of data. The study has presented the different needs in brassiere of selected plus-size women. The following were the conclusions drawn from the results of the survey: 1) The respondents have different needs and encounter various problems in their brassieres and this includes problems regarding brassiere straps pulling into their shoulders and bulges spilling out of the side panels; 2) They have raised concerns on the proper sizing pf plus-size brassieres. They have pointed out that brassieres that are well fit for their frame and support their bust fully should be manufactured; and 3) It has also been indicated that fi8t and quality are the most considered factors related to their purchase of brassieres.